Prayers for the departed: A white elephant in the hymnal of the Evangelical Lutheran Church in Tanzania - Groop, Kim S. (HTS teologiese studies, 2019)
The aim of this article is to study the general and contextual issues related to prayers for the departed with a focus on the Evangelical Lutheran Church in Tanzania (ELCT). In 2012, the ELCT published a new hymnal, which included a number of prayers for those mourning their deceased friends and relatives, as well as prayers for the deceased individuals themselves. As a result of considerable criticism, this hymnal was replaced by a new edition in 2017, in which the prayers for the departed were omitted. The article further scrutinises the historical and theological aspects of praying for the departed in Lutheranism. It studies examples of prayers for the dead in Lutheran churches in two other countries, Finland and Sweden, and relates these to the situation in the ELCT.